Does Proactive Policing Really Increase Major Crime? A Replication Study of Sullivan and O'Keeffe (Nature Human Behaviour, 2017) - Aaron Chalfin; David Mitre-Becerril; Morgan C. Williams (Journal of Comments and Replications in Economics (JCRE), 2024)
In December 2014 and January 2015, police officers in New York City engaged in an organized slowdown of police work to protest the murder of two police officers who were targeted by a gunman while sitting in their patrol car. An influential 2017 article in Nature Human Behaviour studies the effect of the NYPD's work slowdown on major crimes and concludes that the slowdown led to a significant improvement in public safety. Contrary to the remainder of the literature, the authors conclude that proactive policing can cause an increase in crime. We re-evaluate this claim and point out several fatal weaknesses in the authors' analysis - which purports to be a difference- in-differences analysis but isn't - that call this finding into question. In particular, we note that there was considerable variation in the intensity of the slowdown across NYC communities and that the communities which experienced a more pronounced reduction in police proactivity did not experience the largest reductions in major crime. The authors' analysis constitutes a quintessential fallacy in statistical reasoning, a logical miscalculation in which inferences from aggregated data are mistakenly applied to a more granular phenomenon. We raise several additional and equally compelling concerns regarding the tests presented in the paper and conclude that there is little evidence that the slowdown led to short-term changes in major crimes in either direction
https://doi.org/10.15456/j1.2022360.1710041338
Keywords: K42; J18; H70; 330; Proactive policing; Crime